Hydrology drives export and composition of carbon in a pristine tropical river - Travis W. Drake; Matti Barthel; Christian Ekemba Mbongo; Davin Mata Mpambi; Simon Baumgartner; Clement Ikene Botefa; Marijn Bauters; Martin R. Kurek; Robert G. M. Spencer; Amy M. McKenna; Negar Haghipour; Godé Lompoko Ekamba; et al. (Limnology and Oceanography, 2023)
The Ruki is a pristine blackwater tributary in the Congo Basin draining tropical lowland forest. Daily discharge and fortnightly concentrations, isotopic ratios, and molecular composition of carbon and organic matter were measured for 1 yr (2019–2020). Like the Congo River, discharge peaked from November–January, with a smaller secondary peak in June. Dissolved organic carbon (DOC), inorganic carbon (DIC), carbon dioxide ( p CO 2 ), and methane ( p CH 4 ) concentrations were high (21.3 ± 4.8 mg C L −1 , 5.8 ± 0.9 mg C L −1 , 6370 ± 1740 ppm, and 250 ± 100 ppm, respectively) and positively correlated with discharge, indicating transport limitation. Total suspended solids and particulate organic carbon (POC) concentrations were generally low (3.68 ± 1.61 mg L −1 , 0.88 ± 0.33 mg C L −1 , respectively) and varied inversely with discharge, indicating source limitation. The Ruki exported a total of 3.25 Tg C yr −1 , of which DOC, DIC, and POC comprised 76%, 20%, and 3%, respectively. This DOC flux represents ~ 20% of the annual Congo Basin flux from about 5% of its area, highlighting the high yield. Isotopic ratios of DOC and POC indicate modern C3 forest vegetation as a source, except for a few older samples potentially indicating peat inputs. The bulk molecular composition of dissolved organic matter was seasonally consistent; however, a more oxidized and aromatic assemblage occurred at high discharge, corresponding with forest vegetation, while a more aliphatic, nitrogen‐, and sulfur‐enriched assemblage was found during low discharge, corresponding with soil‐derived organic matter. Overall, these results underscore how hydrology controls C concentrations in the Ruki River and how this blackwater river contributes disproportionately to C export per unit area within the Congo Basin hydrosystem.